Desenvolvimento, validação e aplicação de microextração em fase sólida e microextração em fase líquida para determinação de canabinóides em cabelo humano por cromatografia em fase gasosa acoplada à espectrometria de massas no modo tandem - Emídio, Elissandro Soares (2010)
The drug abuse has created several problems, moral, social and economical, and does not have borders of social class, educational and religious. The chemicaltoxicological analysis is an indispensable resource to confirm the exposure of humans to these drugs. Depending on the purpose of analysis, various biological matrices can be used. Nowadays, hair is being recognized as a third fundamental biological sample for drug testing besides urine and blood. The collection of hair samples is simple, noninvasive being difficult its adulteration. The techniques based on the miniaturization of extraction have gained an important role on the world stage in relation to conventional techniques. Among these techniques, stand out to solid phase microextraction (SPME) and liquid phase microextraction (LPME). In this work, a analytical method was developed for determination of 9- tetrahydrocannabinol (9-THC), cannabidiol (CBD) and cannabinol (CBN) in human hair by headspace solid-phase microextraction (SPME) and hollow fiber liquid-phase microextraction (HF-LPME) using gas chromatography coupled to mass spectrometry, operating in tandem mode (GC-MS/MS). Initially, in step sample preparation, a small mass of hair (10 mg) was decontaminated with petroleum ether (2 mL) for 10 minutes of ultrasound application (3 times) followed by alkaline digestion (NaOH 1 M). A univariate design was used for the determination the better condictions of the parameters of HS-SPME: pH (10), temperature (90 °C), mass of hair (10 mg), extraction time (40 min), desorption time (10 min), ionic strength (Na2CO3), saturation time (10 min) and fiber (PDMS). For HF-LPME a fractional factorial design was used in the screening of some variables of this technique followed by central composite design in the evaluation of optimal values of variables. The variables assessed and the optimum values of these were: extraction solvent (butyl acetate), donor phase pH (14), agitation speed (600 rpm), extraction time (20 min), ionic strength (6.8 % m/v) and acceptor phase volume (20 μL). The methods were submitted to the validation process showed good linearity with coefficient of determination (R2) above 0.994. Precision was determined using two different concentrations (upper and lower limits of the linear range) and RSD values were between 6.6 and 16.4 % for HS-SPME and 4.4-13.7% for HF-LPME. Absolute recoveries were in the range 1.1 to 8.7 % (HS-SPME) and 4.4 to 8.9 % (HF-LPME). The limits of detection and quantification ranged between 7-62 pg mg-1 and from 0.0005-0.020 ng mg-1 to HS-LPME and HF-LPME, respectively. The 9-THC showed values of limits of quantification for both methods below the cut-off (LQ ≤ 100 pg mg-1). Finally, the methods developed and validated were applied in determining CBD, 9-THC and CBN in hair samples of patients from a center of rehabilitation for drug addicts. The concentrations were in the range of LD-0.018 ng mg-1 for CBD, LD-232 pg mg-1 for 9-THC and 9-300 pg mg-1 for CBN show the applicability of the method in monitoring studies. The concentration of cannabinoids in the samples ranged from limit of detection to 18 pg mg-1 for CBD, limit of detection to 232 pg mg -1 for 9-THC and 9 to 300 pg mg-1 to CBN demonstrate the applicability of the method in monitoring studies.